Analysis of Huawei's Global Marketing Strategy to Increasing Competitiveness in the International Smartphone Market - Dwiky Fachrul Hidayat; Muhammad Iqbal Surya Ramadhan; Jovano Bondan Prasetyo (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The global smartphone market has become increasingly competitive, particularly in the premium segment where technological innovation and brand reputation play crucial roles. Despite facing U.S. trade restrictions since 2019, Huawei has strengthened its position as a major competitor to Apple, especially in China. This study aims to analyze Huawei’s global marketing strategy in enhancing international competitiveness by examining the role of technological innovation in building consumer trust and influencing purchase intention. Using a qualitative literature review approach, this study analyzes academic studies, market reports, and industry publications from 2018–2025. The findings reveal that Huawei’s competitiveness is driven by premium positioning, technological innovation, and localization strategies. Innovations such as HarmonyOS, proprietary chipsets, artificial intelligence, and flagship smartphones significantly strengthen consumer trust and purchase intention. In China, consumers increasingly prefer Huawei over Apple due to perceptions of technological advancement, domestic innovation, and stronger national brand attachment. These findings suggest that innovation-driven trust and adaptive marketing strategies are key factors in Huawei’s international competitiveness.